Solvent extraction of oil from Arachis hypogaea: the effects of extraction temperature and liquid/solid ratio: article - Shamsudin, Noor Laila; Mohd Fuad, Faiznur (2018)
Solvent extraction is one of techniques that can be used to extract oil. Solvent extraction is more preferable technique compared to the other techniques due to the low cost, simple and faster extraction process. It is also important to explore more sources of vegetable oil as the demand of vegetable oil is increasing rapidly due to its numerous applications. The objectives of this research are to study the effect of different extraction temperatures and the liquid/solid (L/S) ratio on the solvent extraction of Arachis hypogaea oil. Peanut oil was extracted using solvent extraction technique and ethyl acetate was used as solvent. The extraction temperatures were set at 35⁰C, 40⁰C, 50⁰C, and 60⁰C, 70⁰C, and 75⁰C. The samples then were prepared with L/S ratio of 3:1, 4:1, 5:1, 6:1, 7:1 and 8:1. After the solid-liquid and solvent-oil mixture were separated, the oil yield was calculated. The samples were analyzed using Gas Chromatography-Mass Spectrometry, (GC-MS) to determine the chemical constituent. The optimum condition was at the temperature of 70⁰C and L/S ratio of 6:1. The oil yield obtained was 43.8%. The major fatty acid components found in the extracted peanut oil were oleic acid, linoleic acid and palmitic acid.